Phonological awareness training program for brazilian bilinguals deaf children - Souza, Érika Costa de; Bandini, Heloisa Helena Motta (Paidéia (Ribeirão Preto), 2007)
The phonological awareness is required for the acquisition of reading and writing ability. Hearing children increase their levels of phonological awareness and their reading and writing skills when exposed to a formal phonological awareness training program. The effect of this procedures in deaf children is unknown. The aim of this study was create a special phonological awareness training program for bilingual deaf children and to evaluate its effectiveness. Four children were phonological evaluated and selected to participate in the study. The results showed that, after the training, the children's phonological awareness was improved. This study provides evidences that a phonological awareness training can improve the development of phonological awareness in deaf children users of the Sign Language.